Evaluasi Program Pelatihan Kerja Kejuruan Refrigerasi Berbasis Model Kirkpatrick: Studi Kasus di Balai Latihan Kerja Kabupaten Karawang - Mardani Mardani; Enjang Suherman; Laras Ratu Khalida (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This study aims to evaluate the effectiveness of the refrigeration vocational training program at the Job Training Center (BLK) of Karawang Regency using the Kirkpatrick Evaluation Model, which consists of four levels: reaction, learning, behavior, and results. The study employed a descriptive qualitative approach, with data collected through interviews, observations, and documentation. The informants included program managers, instructors, and trainees. Data were analyzed interactively through data reduction, data display, and conclusion drawing. The results indicate that at the reaction level, participants showed positive responses toward the training materials, instructional methods, and instructor competence. At the learning level, there was an improvement in participants’ knowledge and technical skills in accordance with the Indonesian National Work Competency Standards (SKKNI). At the behavior level, participants demonstrated changes in work attitudes, becoming more disciplined, structured, and responsible. At the results level, out of 16 participants, 12 were declared competent and ready for employment or entrepreneurship, while the remaining 4 participants did not meet the established competency standards. These findings suggest that competency-based training at the BLK of Karawang Regency is effective in enhancing participants’ quality and job readiness, and contributes to strengthening the quality of human resources at the local level.